Предмет: Математика,
автор: izel11
Помогите пожалуйста! !!
Приложения:
Ответы
Автор ответа:
0
2x(x^3-y^4)-(2xy^4+x^3)= 2x^4-2xy^4-2xy^4-x^3=2x^4-4xy^4-x^3
(x^4+y^7)^2=x^8+2x^4y^7+y^14
(a-4)^2-2(a-4)(a+4)+(a+4)^2= сворачивается= (а-4-(a+4))^2=(-16)^2=256
(a+2b)^2-(a-2b)^2=(a+2b-(a-2b))(a+2b+a-2b)=4b×2a=8ab
27x^3-8=(3x-2)(9x^2+6x+4)
(x^4+y^7)^2=x^8+2x^4y^7+y^14
(a-4)^2-2(a-4)(a+4)+(a+4)^2= сворачивается= (а-4-(a+4))^2=(-16)^2=256
(a+2b)^2-(a-2b)^2=(a+2b-(a-2b))(a+2b+a-2b)=4b×2a=8ab
27x^3-8=(3x-2)(9x^2+6x+4)
Похожие вопросы
Предмет: Другие предметы,
автор: nastyaluk2010
Предмет: Алгебра,
автор: IsaDm
Предмет: Английский язык,
автор: gulnazabdu
Предмет: Математика,
автор: KuRay
Предмет: География,
автор: Erkenov